El reino del Ponto - Ballesteros Pastor, Luis (Gerión. Revista de Historia Antigua, 2006)
The dynasty of Pontus shared influences from both the Hellenic and Persian civilizations. Therefore, the education of the “crown prince” might have aspects characteristic of the Achaemenid world: hunting on horseback, ordeals with poisons, and survival isolated in the country. However, the information we have reflects that the Greek paideía prevailed. The heir to the diadem, eldest son of the king, had been assigned military tasks as a general, and could be named as governor of some territories under Pontic rule. Together with the heir, it seems that the last Mithridatids gave a special role to another prince, probably to prevent successory troubles.